2019
DOI: 10.1029/2019ja026766
|View full text |Cite
|
Sign up to set email alerts
|

Substorm‐Ring Current Coupling: A Comparison of Isolated and Compound Substorms

Abstract: Substorms are a highly variable process, which can occur as an isolated event or as part of a sequence of multiple substorms (compound substorms). In this study we identify how the low‐energy population of the ring current and subsequent energization varies for isolated substorms compared to the first substorm of a compound event. Using observations of H+ and O+ ions (1 eV to 50 keV) from the Helium Oxygen Proton Electron instrument onboard Van Allen Probe A, we determine the energy content of the ring current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…This criterion is different from earlier substorm studies, which mostly require a quiet time of about 3 hours prior to isolated substorms. As pointed out by Sandhu et al (2019), a stronger solar wind driving was often maintained for several days prior to the compound substorm onsets.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This criterion is different from earlier substorm studies, which mostly require a quiet time of about 3 hours prior to isolated substorms. As pointed out by Sandhu et al (2019), a stronger solar wind driving was often maintained for several days prior to the compound substorm onsets.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, auroral emission in many of these events extended from Lapland to the southern part of the Svalbard archipelago, being observed in the ground-based auroral images there. The inner magnetospheric observations by Sandhu et al (2019) showed that the energy content in the ring current was azimuthally more localised during isolated than compound substorms, leading to smaller-scale substorms. However, they concluded that the latitude (L shell) extent of the enhancements varied less, suggesting that the same would apply to the high-energy part of the substorm precipitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the majority of storms are of similar length, it provides a good framework for studying the average storm-time responses; however, other time-dependent phenomena, such as substorms, are averaged out. It is well known that substorms frequently occur during geomagnetic storms and are important for the energization of the ring current (e.g., Daglis, 2006;Sandhu et al, 2019), but Grocott et al (2009) showed that substorms primarily produce a response in the high-latitude ionospheric convection pattern on the nightside and that ordering by onset location is important when trying to gain insight from the average convection pattern. It thus follows that although substorms commonly occur during geomagnetic storms, we do not see their signatures.…”
Section: 1029/2020ja028512mentioning
confidence: 99%
“…Instead of the AL, Partamies et al (2015) used a regional electrojet index (an IL version they called IL ASC ) constructed from baselined data collected at five Lapland magnetometer stations of the IMAGE network (Tanskanen, 2009) E). The selected stations were co-located with the MIRACLE auroral all-sky cameras (Sangalli et al, 2011), allowing the auroral morphology to be analysed over the same area. They also concluded that the long-term median value of −50 nT was valid for this regional index as well.…”
Section: Magnetic Activity Indices and Substorm Phase Detectionmentioning
confidence: 99%